The impact of Zoom as a learning application on student learning concentration in the COVID-19 era - Fuad Azhar Makarim El Yusuf; Tasya Susanti (Curricula: Journal of Curriculum Development, 2022)
The presence of COVID-19 has hampered the activities carried out by the community, one of which is in the field of education. With the entry of the era of the Industrial Revolution 4.0, education must follow technological developments and take advantage of technological sophistication to facilitate the learning process. Today there are many technological innovations in the world of education, for example, in the form of applications or learning platforms that can support the learning process between educators and students. This study aims to determine the effect of the ZOOM learning application in the COVID-19 era on students' learning concentration. The study used descriptive quantitative methods with survey activities as data collection, involving students from junior high school, senior high school, vocational school, and university level as respondents. The results showed differences in students' level of concentration during distance learning and face-to-face learning. After participating in distance learning assisted by the ZOOM video conferencing application, the concentration of students decreased to focus on learning. So it can be concluded that the ZOOM application influences the concentration of student learning during the COVID-19 pandemic. It is hoped that increasingly advanced technological developments can help students concentrate on learning.